Borders without barriers facilitating trade in SASEC countries. - Abdou, Marwa (Asian Development Bank, 2019)
Presents an analysis of the state of trade facilitation in member countries of the South Asia Subregional Economic Cooperation (SASEC) programme. The book includes country-level studies and identifies four common trade facilitation priorities among SASEC countries